"I want to be a furious leopard with magical wings and super power": developing an ethico-interpretive framework for detecting Chinese students' funds of identity - Poole, Adam (Cogent OA, 2017)
The Avatar Project was a two-week English project in which Chinese high school students in an internationalised school in Shanghai China explored the topic of cultural and individual identity. The project synthesised prospective education with the Funds of Identity approach, both of which have particular relevance within an internationalised teaching context. During the project, students created three identity texts: a written reflection, a word cloud and an avatar which were later used as data for this article. This article presents findings from the project and critically evaluates the effectiveness of avatars and word clouds as strategies for detecting students’ funds of identity. A multimodal approach to data collection and analysis was adopted in order to ensure that the interpretation of students’ work remained situated within their lived experience. The project revealed the existence of social, practical, institutional and cultural funds of identity. However, it also detected more problematic forms of funds of identity related to political and philosophical beliefs which I label ideological and existential funds of identity. While avatars and word clouds were effective in drawing out students’ out-of-school identities, the written reflections were ultimately more useful in revealing students’ funds of identity and also ensuring that any interpretations remained within the participants’ horizon of intended meaning. The project also brought about significant transformation in the way I viewed my students.